Keragaan Serangan Hama dan Penyakit serta Hasil Tiga Varietas Unggul Baru Padi pada Display Teknologi Pengendalian Hayati - Kusmea Dinata; Monita Puspitasari; Irma Calista; Yulie Oktavia; Siti Rosmanah; Yahumri Yahumri; Hendri Suyanto; Shannora Yuliasari; Yudi Sastro (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Dinata K, Puspitasari M, Calista I, Oktavia Y, Rosmanah S, Yahumri Y, Suyanto H, Yuliasari S, Sastro Y. 2021. Performance of pests and diseases attack and yield of three new superior varieties of rice on biological control technology display. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 555-562. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Rice is a strategic food commodity whose needs are always increasing. Currently, food security and food safety must be carried out in order to ensure the availability of healthy food for consumption. One of the input factors for pollution to health is the excessive use of synthetic chemical pesticides in the production process in the field. In an effort to control pests and plant diseases, the government has implemented an integrated pest control program (IPM), but this technology has not yet been developed. The purpose of this study was to determine the ability of several rice varieties and the use of biological agents in suppressing pest attacks on rice plants. The study was conducted in a randomized block design with two paired treatments, namely the use of biological agents and synthetic chemicals on three new high yielding varieties of lowland rice This research was carried out on the cooperator farmer's land area of 1 ha. The technological components applied are the use of three New Superior Varieties (Inpari Digdaya, Inpari IR Nutri Zinc and Inpari 46) and biological control. The results showed that the main pest and disease attacks on the treatment of biological agents and synthetic chemicals were not significantly different. However, in the treatment of using new superior varieties, there was a significant difference in the intensity of panicle neck blast disease from the three varieties. The Inpari 46 variety has the highest productivity compared to the other two varieties.